Analysis of the ceramic coatings' recrystallization produced on the surface of the Zr-25Ta-25Ti alloy - Kuroda, Pedro Akira Bazaglia; de Mattos, Felype Narciso; Grandini, Carlos Roberto [UNESP]; Afonso, Conrado Ramos Moreira (Elsevier, 2024)
The objective of this study is to analyze the influence of the heat treatment temperature carried out at ultra-high vacuum on surfaces formed in the Zr-25Ta-25Ti alloy by the micro-arc oxidation (MAO) technique to produce a ceramic layer with high hardness and high wear resistance. The results of structural (XRD) and microstructural characterization (SEM, optical and confocal microscopy technique) show that the surfaces are mainly composed of zirconium dioxide (ZrO2), Ti2ZrO, and calcium oxide (CaO). The heat treatments at high temperatures (500–800 °C) altered the phases of the MAO coating, forming ZrC. Confocal images showed that increasing temperature increased the roughness of the coatings (0.65 → 1.06 μm). Consequently, the topography of the coatings, wettability, microhardness (Vickers), and wear resistance (obtained by the ball cratering technique) of the materials are also modified. The wear results show that the MAO coating has a low wear rate value due to the MAO surfaces’ high hardness, efficiently protecting the substrates of the Zr-25Ta-25Ti alloy against tribological phenomena. Finally, the increase in heat treatment temperature promoted the formation of cracks in the coatings due to the difference in thermal expansion of the MAO ceramic with the Zr-25Ta-25Ti alloy substrate, causing a decrease in the hardness value and reducing wear resistance.
Keywords: Heat treatment; Micro arc oxidation; Zr-25Ta-25Ti alloy